Effectiveness Model Blended Learning AMIR (Augmentation, Modification, Interactive, Reflection) Based on Edu Virtual Laboratory History - Amirullah, Amirullah; Manda, Darman; Kamaruddin, Syamsu A. (PT ARRUS Intelektual Indonesia, 2025)
This research aims to: To describe the effectiveness of blended learning model based on Edu Virtual Laboratory History. And produce model book products and learning tools in improving the effectiveness of history learning. This research is an R&D research by adopting the 4-D model design (define, design, Develop and Disseminate). Data collection techniques were observation, interview, test, questionnaire and documentation. This research uses learning implementation observation instruments, student learning outcomes assessment tests and learning tool validation sheets. The data analysis technique was carried out by (1) analysing the level of validity (2) analysing the level of practicality, (3) analysing student and lecturer response data. The results of this study indicate that the need for the development of a Blended Learning model based on Edu Virtual laboratory History, to increase the effectiveness of history learning. The results of the validation test showed that the model book, implementation guide, learning tools and research questionnaires were declared valid based on the assessment.